Functional Outcome of Complex Tibial Plateau Fracture Treated by Dual Plating - Mishra, Anil Kumar; Adhikari, Vijayendra; Chalise, Prahlad Kumar; Shrestha, Praphulla; Singh, Ramesh Prasad (Nepal Orthopaedic Association Journal, 2019)
INTRODUCTION: Tibial Plateau fractures are very complex due to involvement of joint and the metaphyseal region. Among tibial plateau fracture, 35.8% accounts for bicondylar tibial plateau fracture, which consists of Schatzker type V and VI. Open reduction with minimal soft tissue dissection and fixation of fracture with dual plating is the treatment of choice. The aim of our study is to assess the functional outcome and complication after the fixation of bicondylar tibial plateau fracture with dual plating.METHODS: The study included total of 30 patients with bicondylar tibial plateau fractures who met the inclusion criteria, were treated with open reduction and internal fixation with dual plates. Bicondylar tibial plateau fractures includes both Schatzker type V (n= 17) and Type VI (n=13).RESULTS: Knee society score in Schatzker type V out of 17 patients, 9 had excellent results, 7 had good results and 1 had fair results. Knee society score in Schatzker type VI out of 13 pa-tients, 7 had excellent results, 4 had good results and 2 had fair results. Among the 30 pa-tients, we found superficial wound infection in 3 patients during the follow up.CONCLUSION: The high energy Schatzker type V and VI tibial plateau fractures using double plate fixation through dual incision technique provides stable fixation, a minimal soft tissue dissection with satisfactory functional outcome and low complication rates.